Functional Preservation and Quality of Life in Head and Neck Radiotherapy - Harari, P. M.; Connor, N. P.; Grau, C. (Medical Radiology, 2009)
This book focuses on functional treatment outcomes in head and neck cancer patients from the perspective of experts from around the world in medical and allied health fields. Recent advances in management strategies are presented as they relate to functional preservation and quality of life. Clinical and research knowledge is organized in an approachable manner by means of short chapters, key point tables, and high-quality illustrations and graphics. This method of presentation is very effective for busy clinical practitioners and researchers. Information is provided on site-specific epidemiology and treatment outcome, the impact of different treatment techniques and toxicities on quality of life, and the relationship of toxicity prevention, rehabilitation, and supportive care to quality of life after treatment, Among literature on the treatment of head and neck cancer, this book is unique because of the outstanding list of contributors and the specific focus on functional preservation and quality of life.